Evaluation of Carbon Sequestration and Global Warming Potential of Wheat in Khorasan-Razavi province - Surur Khorramdel; Javad Shabahang; Raheleh Ahmadzadeh Ghavidel; Abdollah Mollafilabi (agriTECH, 2018)
In order to determine soil characteristics and above-ground and below-ground carbon sequestration potential of wheat, a systematic random sampling method was employed to select 5 samples from 50 fields situated in Khorasan-Razavi Province, Iran during 2015. The experimental design was a completely randomized design with three replications. The ash method was used to determine the carbon sequestration conversion coefficients in spikes, stems, leaves and roots. Then, greenhouse gases (such as CO2, N2O and CH4) emission were calculated using emission coefficients. The average organic carbon, total nitrogen, available phosphorus, available potassium, soil bulk density, pH and electrical conductivity were found to be 0.98%, 0.02%, 27.07 ppm, 341.32 ppm, 1.37 g.cm-3, 7.81 and 1.42 dS.m-1, respectively. The maximum (52.0%) and minimum (31.99%) conversion coefficients were related to spikes (seeds included) and roots, respectively. In addition, the total carbon sequestration was 8.25 t.ha-1 so that the maximum (4.28 t.ha-1) and minimum (0.35 t.ha-1) values were found in stems and roots, respectively. The total global warming potential (GWP) of wheat was recorded as 2377.86 kg CO2 –equiv. per ton of seed. The first contributing factor was nitrogen fertilizers, accounting for 1331.30 kg CO2 –equiv. per ton of seed.